2003
DOI: 10.1002/ceat.200300050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Particles on Fluid Turbulence in Pipe and Diffuser Gas‐Solids Flow

Abstract: The influence of glass particles with different Reynolds numbers Re P = ½u±u P ½d P r/g on axial and radial gas fluctuations as well as on Reynolds stresses was investigated for pipe and diffuser (continuous pipe expansion) gas-solids flow. Measurements were carried out using phase-Doppler anemometry distinguishing between velocity signals of the solid and fluid phase due to particle or tracer size. In fully developed pipe flow small particles (Re P = 60) damp turbulence but with increasing Re P vortex sheddin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The Kolmogorov scale is the characteristic scale at which eddies decay due to viscous dissipation, the Taylor microscale is characteristic of the inertial range eddies, and the integral length scale is characteristic of the large, energy-containing eddies. Turbulence quantities for single and two-phase flows are measured by Tsuji et al [37] and Bohnet and Triesch [38] for pipe flow with a similar Reynolds number and diameter to that reported in the current experiments. These studies found that the ratio u 0 /U varies between 0.05 and 0.1 for pipe turbulence, giving on average q ∼ = 0.008U 2 .…”
Section: Sensor Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…The Kolmogorov scale is the characteristic scale at which eddies decay due to viscous dissipation, the Taylor microscale is characteristic of the inertial range eddies, and the integral length scale is characteristic of the large, energy-containing eddies. Turbulence quantities for single and two-phase flows are measured by Tsuji et al [37] and Bohnet and Triesch [38] for pipe flow with a similar Reynolds number and diameter to that reported in the current experiments. These studies found that the ratio u 0 /U varies between 0.05 and 0.1 for pipe turbulence, giving on average q ∼ = 0.008U 2 .…”
Section: Sensor Analysissupporting
confidence: 80%
“…The distinction between the two is determined by the ratio of the particle diameter to the turbulence integral length scale , such that for d/ < 0.1 the turbulence is attenuated by the particles [40]. A review of recent research on effects of particles on turbulent pipe flow is given by Bohnet and Triesch [38]. Assuming that the particle relative velocity is of the same order of magnitude as the average air velocity, the particle Reynolds number varies from about 40 to 630 for the current experiments, and the ratio d/ varies between 0.023 and 0.11.…”
Section: Sensor Analysismentioning
confidence: 99%
“…The code was validated with different experiments [41,44,58].This validation ensure how the code can be accurate for the experiment data. The geometry of the diffusers have many variables such as inlet radius, outlet radius, length of diffuser and angles.…”
Section: Validation Of Codementioning
confidence: 99%
“…For the particles diameters, we use the same parameters in experiment [41], the angle of diffuser 6°…”
Section: Effect Of Particles Diametersmentioning
confidence: 99%
See 1 more Smart Citation